2000
DOI: 10.1095/biolreprod62.5.1135
|View full text |Cite
|
Sign up to set email alerts
|

Development Rates of Male Bovine Nuclear Transfer Embryos Derived from Adult and Fetal Cells1

Abstract: This study compared the nuclear transfer (NT) embryo development rates of adult and fetal cells within the same genotype. The adult fibroblast cells were obtained from a 21-yr-old Brahman bull. The fetal cells were derived from a Day 40 NT fetus previously cloned using cells from the Brahman bull. Overall, similar numbers of blastocysts developed from both adult (53 of 190; 28%) and fetal (39 of 140; 28%) donor cells. Improved blastocyst development rates were observed when fetal cells were serum-starved (seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
0
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(115 citation statements)
references
References 26 publications
10
101
0
4
Order By: Relevance
“…Our results were in agreement with the previous report in cattle that the nuclei of serum starved fibroblasts support the development of reconstructed embryos to the blastocyst stage significantly better than those of nonstarved fibroblasts (39% vs. 20%) [38]. Serum starvation of fetal donor cells before NT was also found to significantly improve NT blastocyst rates when compared with serum fed cells (43% vs. 12%) [39].…”
Section: Discussionsupporting
confidence: 92%
“…Our results were in agreement with the previous report in cattle that the nuclei of serum starved fibroblasts support the development of reconstructed embryos to the blastocyst stage significantly better than those of nonstarved fibroblasts (39% vs. 20%) [38]. Serum starvation of fetal donor cells before NT was also found to significantly improve NT blastocyst rates when compared with serum fed cells (43% vs. 12%) [39].…”
Section: Discussionsupporting
confidence: 92%
“…This was in agreement with studies showing that the age, size, gender and type of donor cell may affect the efficiency of SCNT (4,(14)(15)(16). Moreover, culturing donor cells for long time periods resulted in decreased rates of in vitro embryos and to term development in cattle (17). Altogether, these studies indicate that nuclear donor cell preparation is a crucial step affecting the developmental potential of reconstructed embryos and the successful production of transgenic animals by SCNT.…”
Section: Discussionsupporting
confidence: 90%
“…Most of these efforts are focused on donor cells. These include: (a) synchrony of the cell cycle stage of donor cells (Kasinathan et al, 2001;Gibbons et al, 2002;Wells et al, 2003), as well as synchrony between donor cells and recipient oocytes (Campbell et al, 1994;Du et al, 2002); (b) using somatic cells from donors of various ages (Renard, 1999;Hill et al, 2000;Tian et al, 2000;Kasinathan et al, 2001;Xue et al, 2002), tissue origins (Galli et al, 1999;Shiga et al, 1999;Kato et al, 2000;Ogura et al, 2000;Du et al, 2002;Hochedlinger and Jaenisch, 2002;Miyashita et al, 2002), passages (Shiga et al, 1999;Arat et al, 2001;Liu et al, 2001) and culture conditions (Zakhartchenko et al, 1999b); (c) transfer of stem cells with low levels of epigenetic marks (Kato et al, 1999a;Wakayama et al, 1999;Amano et al, 2001;Eggan et al, 2001;Humpherys et al, 2001;Zhou et al, 2001); and (d) modifying epigenetic marks of donor cells with drugs (Jones et al, 2001;Zhou et al, 2002;Enright et al, 2003). Wilmut et al (2002) reported that a number of cellular factors influence the outcome of cloned offspring.…”
Section: Introductionmentioning
confidence: 99%